Interest-rate-growth differentials and government debt dynamics - Turner, David (OECD Publishing, 2012)
The differential between the interest rate paid to service government debt and the growth rate of the economy is a key concept in assessing fiscal sustanability. Among OECD economies,this differential was unusually low for much of the last decade compared with the 1980s and the first half of the 1990s. This article investigates the reasons behind this profile using panel estimation on selected OECD economies as means of providing some guidance as to its future development. The results suggest that the fall is partly explained by lower inflation volatility associated with the adoption of monetary policy regimes credibly argeting low inflation,which might be expected to continue. However,the low differential is also partly explained by factors which are likely to be reversed in the future,including very low policy rates,the "global savings glut" and the effect which the European Monetary Union had in reducing long-term interest differentials in the pre-crisis period. The differential is also likely to rise in the future because the number of countries which have debt-to-GDP ratios above a threshold at which there appears to be an effect on sovereign risk premia has risen sharply. Moreover,debt is projected to increasingly rise above this threshold in most of these countries
Keywords: Economics